'I know that I'm in my own world; it's OK, they know me here': the challenge of coping with FASD in educational settings. (October 2015) - Roberts, Brian
In July 2012, the UK's All Party Parliamentary Group published their long-awaited report into the educational attainment of looked after children. This report included 10 key recommendations to improve practice. One was that 'teachers should receive greater training to improve their understanding of and ability to manage issues such as trauma, attachment and Foetal Alcohol Spectrum Disorders (FASD)'. Members of the working group understood that these conditions can have significant and lifelong effects on the education and life chances of children who have been in care. It could be argued that of the three conditions listed, FASD may well be the most significant but is often the most overlooked and misunderstood. FASD can place a significant barrier to learning, but currently is so poorly understood that teachers and schools struggle to provide the best learning environments.